2011
DOI: 10.1177/0269881111408966
|View full text |Cite
|
Sign up to set email alerts
|

Complexity analysis of spontaneous brain activity: effects of depression and antidepressant treatment

Abstract: Magnetoencephalography (MEG) allows the real-time recording of neural activity and oscillatory activity in distributed neural networks. We applied a non-linear complexity analysis to resting-state neural activity as measured using whole-head MEG. Recordings were obtained from 20 unmeditated patients with major depressive disorder and 19 matched healthy controls. Subsequently, after 6 months of pharmacological treatment with the antidepressant mirtazapine 30mg/day, patients received a second MEG scan. A measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(64 citation statements)
references
References 38 publications
(46 reference statements)
2
60
2
Order By: Relevance
“…In previous studies, we found that age and gender might be modifying factors of LZC values (Fernández et al, 2011a;Méndez et al, 2011). Thus, our study began with an exploratory analysis by describing data according to these two variables.…”
Section: Age and Gender Effects On Lzcmentioning
confidence: 98%
See 4 more Smart Citations
“…In previous studies, we found that age and gender might be modifying factors of LZC values (Fernández et al, 2011a;Méndez et al, 2011). Thus, our study began with an exploratory analysis by describing data according to these two variables.…”
Section: Age and Gender Effects On Lzcmentioning
confidence: 98%
“…No significant differences in terms of age were found between males (42.26 ± 21.08) and females (45.11 ± 22.05). All participants included in the current investigation have been described in some of our previous studies (Fernández et al, 2002;Fernández et al, 2009;Fernández et al, 2010;Fernández et al, 2011a;Méndez et al, 2011;Solesio et al, 2009). …”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations